Adapting flexible metadata support in Dataverse to the needs of domain-specific repositories – the case of The Tromsø Repository of Language and Linguistics (TROLLing) - Conzett, Philipp; Andreassen, Helene N. (2021)
Presentation at the online Knowledge Organization Research Observatory (KO-RO) seminar, 24.11.21, arranged by The UK Chapter of the International Society for Knowledge Or. https://www.iskouk.org/event-4527328 The Tromsø Repository of Language and Linguistics (TROLLing; https://trolling.uit.no/) is an international repository of data, code, and other related materials used in linguistic research. Established in 2014, TROLLing has since 2020 been CoreTrustSeal-certified as a sustainable and trusted research data repository. Running on the Dataverse software (https://dataverse.org/), TROLLing has so far been using a more general metadata schema which is provided by the repository software. Drawing on the work being done in projects like SSHOC (https://www.sshopencloud.eu/) and CLARINO+ (https://clarin.w.uib.no/about/), the metadata schemas in TROLLing are being upgraded to meet the needs of our designated community, and the requirements and recommendations of international stakeholders like CLARIN (Common Language Resources and Technology Infrastructure; https://www.clarin.eu/) and the Research Data Alliance Linguistics Data Interest Group (https://rd-alliance.org/groups/linguistics-data-ig). The presentation will include a short introduction to TROLLing and discuss how community-driven efforts enable the repository to provide FAIR-aligned domain-specific support for linguists worldwide.